Hubungan Dukungan Sosial Dengan Psychological Well Being Pada Mahasiswa Rantau Di Universitas Muhammadiyah Pontianak: Hubungan Dukungan Sosial Dengan Psychological Well Being Pada Mahasiswa Rantau Di Universitas Muhammadiyah Pontianak - Apriani, Desi; Vidyastuti; Riszky Ramadhan (Psikodinamika: Jurnal Literasi Psikologi, 2025)
Overseas students are individuals who pursue their education at a university located outside their home region, requiring them to reside in that area for a certain period to complete their studies. This research aims to examine the relationship between social support and the psychological well-being of overseas students at Universitas Muhammadiyah Pontianak. These students often face various challenges, including academic pressure and feelings of loneliness, which can affect their psychological well-being. The study involved 110 overseas students and hypothesized that greater social support, whether from family, friends, or the community, would be positively associated with better psychological well-being. The research used social support and psychological well-being scales to measure the relationship between the two variables in overseas students at Universitas Muhammadiyah Pontianak. The data were analyzed using the Spearman Rank correlation technique with SPSS version 25.0. The results showed a significant and positive relationship between social support and psychological well- being. In other words, the more social support the students received, the better their psychological well-being. Both variables were categorized as moderate, indicating that the levels of social support and psychological well-being were average. The study demonstrated that social support contributed 57.6% to the psychological well-being of overseas students, while the remaining 42.4% was influenced by other factors such as personality, stress, and economic conditions. The higher the social support received by overseas students, the better their psychological well-being.